Risk and Protective Factors Associated With Suicide Attempts: A Qualitative Study Among Hospitalized Patients in Turkey - Siraz, Mehmet Fatih; Eryilmaz, Ali; Yildirim-Kurtulus, Hacer; Bozdas, Mehmet Sabri; Yildirim, Murat (WILEY, 2025)
Aim This study aimed to investigate the contributing factors to suicidal behavior and to gather insights from individuals who have attempted suicide regarding potential clinical, psychosocial, and family-based prevention resources.Design A qualitative research design was employed to explore participants' lived experiences and perceptions surrounding suicidal behavior.Methods Data were collected through semi-structured interviews with 12 individuals (four men and eight women) who had previously attempted suicide, selected using purposive sampling. All participants were admitted to the Emergency Department of a public hospital in Kayseri immediately following their suicide attempts and were subsequently referred to the inpatient psychiatry service for treatment. The data were analyzed using Interpretative Phenomenological Analysis (IPA) to explore participants' lived experiences and meanings. Frequency counts of emergent themes and subthemes were also noted to illustrate their relative prominence, but IPA remained the primary analytic approach.Results Three main themes emerged from the data: individual, environmental, and relational factors. Individual factors included risk elements such as irrational beliefs, negative emotions, and physical health problems, as well as protective factors like emotional regulation, religious beliefs, and medication use. Environmental factors encompassed financial difficulties and lack of social support as risks, with the presence of social support acting as a protective element. Relational factors involved betrayal, arguments, violence, and punitive desires as risks, while commitment to family members served as a protective factor. Overall, protective factors such as religious beliefs, social support, and family connectedness appear to be particularly effective in reducing suicidal thoughts.Patient or Public Contribution Participants with lived experience of suicide attempts made unique contributions to this study by sharing their first-hand perspectives on the personal, social, and relational contexts of suicidal behavior. Their narratives not only shaped the thematic analysis but also highlighted prevention opportunities such as strengthening family connectedness and enhancing social support that may not have emerged through quantitative approaches alone.
Keywords: protective factors; qualitative study; risk factors; suicide attempts; HOPELESSNESS; DEPRESSION; METAANALYSIS; IDEATION; INTERVIEWS; BEHAVIORS; THOUGHTS; PEOPLE; DEATH; Nursing